Front Cover: Catalytic Pyrolysis of Polyethylene with Microporous and Mesoporous Materials: Assessing Performance and Mechanistic Understanding (ChemSusChem 7/2025) - Minkelis, Johan H.; Hergesell, Adrian H.; Waal, Jan C.; Altink, Rinke M.; Vollmer, Ina; Weckhuysen, Bert M. (ChemSusChem, 2025)
The Front Cover shows a mesoporous catalyst for the chemical recycling of polyethylene. The large pores allow full penetration of the catalytic system to effectively utilize its active surface, as opposed to microporous materials whose activity is often limited by the insufficient transport of large macromolecules. A sulfated zirconia on SBA‐15 catalyst allowed I. Vollmer, B. M. Weckhuysen and co‐workers to investigate the intrinsic catalytic properties without being limited by pore accessibility. More information can be found in their Research Article (DOI: 10.1002/cssc.202401141).